2019
DOI: 10.1001/jamanetworkopen.2019.7084
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preterm Births Among US Latina Women With the 2016 Presidential Election

Abstract: Key Points Question Did preterm births increase among Latina women who were pregnant during the 2016 US presidential election? Findings This population-based study used an interrupted time series design to assess 32.9 million live births and found that the number of preterm births among Latina women increased above expected levels after the election. Meaning The 2016 presidential election may have been associated with adverse hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(138 citation statements)
references
References 31 publications
9
128
0
1
Order By: Relevance
“…The 2016 US presidential election has been linked to increases in psychological distress, and short term mood changes following the election associated with more sustained physiological stress responses among young adults 2223. Studies have also shown an increase in psychological concerns and preterm births among Latina women following the 2016 election 2425. Along with our data, this suggests that large scale political events can influence factors relevant to mental and physical health, particularly for those with specific concerns about how the events may affect their lives.…”
Section: Discussionmentioning
confidence: 99%
“…The 2016 US presidential election has been linked to increases in psychological distress, and short term mood changes following the election associated with more sustained physiological stress responses among young adults 2223. Studies have also shown an increase in psychological concerns and preterm births among Latina women following the 2016 election 2425. Along with our data, this suggests that large scale political events can influence factors relevant to mental and physical health, particularly for those with specific concerns about how the events may affect their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Despite accumulating evidence of deportation fears among Latino U.S. citizens and noncitizens, we know surprisingly little about whether and how these fears manifest nationally and over time. Research using population-representative administrative or survey data has linked changes to deportation policy or practice with negative consequences for Latino U.S. citizens' and noncitizens' behavioral (21)(22)(23)(24)(25)(26)(27), mental health (28)(29)(30)(31)(32), and physical health (33)(34)(35). In each study, a structural factor-for example, the national deportation rate-is linked to an outcome of interest-such as increased rates of psychological distress-and deportation fear is assumed to underlie any observed association.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies described an increase in preterm births among Latina women after the 2016 presidential election. 27,28 Additionally, 400 US-born Latinx adolescents experienced increases in anxiety symptoms in the year after the presidential election. 29 Our results add to this evidence describing the negative effects of restrictive federal immigration policies on Latinx children and particularly those lacking legal documentation.…”
Section: Discussionmentioning
confidence: 99%